Conducting research with Indigenous Peoples in Canada: ethical and policy considerations - Morisano, Dominique; Robinson, Margaret; Rush, Brian; Linklater, Renee (Frontiers in Psychology, 2024)
The international context of Indigenous mental health and wellbeing has been shaped by a number of key works recognizing Indigenous rights. Despite international recognitions, the mental health and wellness of Indigenous Peoples continues to be negatively affected by policies that ignore Indigenous rights, that frame colonization as historical rather than ongoing, or that minimize the impact of assimilation. Research institutions have a responsibility to conduct ethical research; yet institutional guidelines, principles, and policies often serve Indigenous Peoples poorly by enveloping them into Western knowledge production. To counter epistemological domination, Indigenous Peoples assert their research sovereignty, which for the purposes of this paper we define as autonomous control over research conducted on Indigenous territory or involving Indigenous Peoples. Indigenous sovereignty might also be applied to research impacting the landscape and the web of animal and spiritual lives evoked in a phrase such as “all my relations.” This narrative review of material developed in the Canadian context examines the alignment with similar work in the international context to offer suggestions and a practice-based implementation tool to support Indigenous sovereignty in research related to wellness, mental health, and substance use. The compilation of key guidelines and principles in this article is only a start; addressing deeper issues requires a research paradigm shift.